Determinants of global spillovers from US monetary policy - Georgios Georgiadis (European Central Bank (ECB), 2015)
This paper assesses the global spillovers from identified US monetary policy shocks in a global VAR model. US monetary policy generates sizable output spillovers to the rest of the world, which are larger than the domestic effects in the US for many economies. The magnitude of spillovers depends on the receiving country's trade and financial integration, de jure financial openness, exchange rate regime, financial market development, labor market rigidities, industry structure, and participation in global value chains. The role of these country characteristics for the spillovers often differs across advanced and non-advanced economies and also involves non-linearities. Furthermore, economies which experience larger spillovers from conventional US monetary policy also displayed larger downward revisions of their growth forecasts in spring 2013 when the Federal Reserve upset markets by discussing tapering off quantitative easing. The results of this paper suggest that policymakers could mitigate their economies' vulnerability to US monetary policy by fostering trade integration as well as domestic financial market development, increasing the flexibility of exchange rates, and reducing frictions in labor markets. Other policies - such as inhibiting financial integration, industrialisation and participation in global value chains - might mitigate spillovers from US monetary policy, but are likely to reduce long-run growth.
Keywords: F4; E5; C3; 330; Mixed cross-section global VAR; Spillovers; US monetary policy